The Influence of Motivation, Training and Compensation on Employee Performance - Matmuar, Yafet Daniel; Akbar, Muhammad Aldrin; Mustajab, Duta (The Journal of Business and Management Research, 2024)
Purpose: This study aims to analyze the effects of competence, training, and work discipline on the performance of Village Consultative Body (BAMUSKAM) members in Sarmi District. Research Design and Methodology: The research employs a quantitative approach with a survey method, utilizing a questionnaire as the instrument. The sample consists of 56 BAMUSKAM members from Sarmi District. Data analysis was conducted using multiple regression analysis and hypothesis testing with SPSS version 26.0. Findings and Discussion: The results indicate that competence, training, and work discipline each have a positive and significant impact on BAMUSKAM members' performance. Additionally, the combined influence of these variables significantly enhances performance. The findings support the hypothesis that these factors are crucial for improving organizational performance, highlighting the importance of educational and training programs, performance measurement systems, and strict adherence to discipline. Implications: This study underscores the necessity for local governments to invest in comprehensive training and development programs that cater to their specific needs. It also suggests fostering partnerships with educational institutions and implementing robust performance measurement systems that emphasize competence and discipline. The research provides practical insights for local government officials and policymakers to enhance the effectiveness of BAMUSKAM members.